Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Scandium triflate catalyzed unexpected cleavage of C-C bonds in ynones - Kavthe, Rahul D.; Bansode, Avinash H.; Patil, Nitin T. (Arkivoc, 2016)
An unexpected C-C bond cleavage in ynones in the presence of catalytic amounts of Sc(OTf)(3) in methanol under microwave irradiation has been discussed. The effect of substituent on the regioselectivity of C-C bond cleavage has carefully been addressed by employing various ynones derivatives. The mechanism has been proposed for the observed regioselectivity.
Keywords: C-C bond cleavage; Esters; Ketones; scandium triflate; ynones